Motivation factors affecting the job attitude of medical doctors and the organizational performance of public hospitals in Warsaw, Poland - Malgorzata Chmielewska; Jakub Stokwiszewski; Justyna Filip; Tomasz Hermanowski (BMC, 2020)
Abstract Background This paper examines the relationship between selected motivation factors that affect the attitude to work among medical doctors at public hospitals and the organizational performance of hospitals. Methods This study was based on World Health Organization questionnaires designed to estimate motivation factors according to Herzberg's motivation theory and to measure the level of organizational performance of hospitals by using the McKinsey model. A survey was conducted among physicians (n = 249) with either surgical (operative) or nonsurgical (conservative) specialty in 22 departments/units of general public hospitals in Warsaw, Poland. The relationship between the chosen job motivation factors and organizational effectiveness was determined using Spearman's rank correlation. Furthermore, 95% confidence intervals were calculated. The independent samples t-test was used to confirm statistically significant differences between the independent groups. Normality of the data was tested by the Kolmogorov-Smirnov test. Results The survey revealed that motivation factors related to "quality and style of supervision" have the highest effect on the organizational performance of hospitals (Spearman's rank correlation coefficient = 0.490; p < 0.001), whereas "performance feedback" has the lowest effect on organizational performance according to the surveyed healthcare professionals (54% of physicians). Conclusion The principles of Individual Performance Review should be incorporated into strategies designed to improve the organizational performance of hospitals (with NHS serving as a potential role model) in order to establish specific rules on how to share performance feedback with individual physicians. The present study contributes to literature on human resource management in the healthcare sector and highlights the importance of nonfinancial aspects in improving the organizational performance of hospitals.